2021
DOI: 10.1021/acsnano.1c07470
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive and Highly Multiplexed Five-Color Tumor Imaging of Multicore Near-Infrared Resonant Surface-Enhanced Raman Nanoparticles In Vivo

Abstract: In vivo multiplexed imaging aims for noninvasive monitoring of tumors with multiple channels without excision of the tissue. While most of the preclinical imaging has provided a number of multiplexing channels up to three, Raman imaging with surface-enhanced Raman scattering (SERS) nanoparticles was suggested to offer higher multiplexing capability originating from their narrow spectral width. However, in vivo multiplexed SERS imaging is still in its infancy for multichannel visualization of tumors, which requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…Due to the LSPR effect of AuNPs, the intensity of Raman signals for adsorbed molecules is enhanced dramatically, allowing them to be detected at extremely low concentrations . Some groups have utilized near-infrared (NIR) resonant Raman dyes to provide additional enhancement when utilized with a NIR laser, , but these resonant SERS NPs exhibit a high-fluorescence background and crowded Raman spectra, which are both properties known to negatively impact the conditioning of a multiplexed system and contribute to degraded performance at higher plexities. Narrow peaks, low background, and unique molecular fingerprints make SERS NPs labeled by small organic molecules one of the best candidates for extracting highplex data from a single biological sample, animal model, or patient .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the LSPR effect of AuNPs, the intensity of Raman signals for adsorbed molecules is enhanced dramatically, allowing them to be detected at extremely low concentrations . Some groups have utilized near-infrared (NIR) resonant Raman dyes to provide additional enhancement when utilized with a NIR laser, , but these resonant SERS NPs exhibit a high-fluorescence background and crowded Raman spectra, which are both properties known to negatively impact the conditioning of a multiplexed system and contribute to degraded performance at higher plexities. Narrow peaks, low background, and unique molecular fingerprints make SERS NPs labeled by small organic molecules one of the best candidates for extracting highplex data from a single biological sample, animal model, or patient .…”
Section: Resultsmentioning
confidence: 99%
“…After successfully demonstrating 26-plex imaging in vitro , we evaluated the multiplexing capability of our SERS NPs in conjunction with Raman microscopy and spectral unmixing algorithms applied for in vivo imaging. Several reports discuss the potential of utilizing SERS NPs for in vivo clinical applications using either active or passive tumor targeting. ,, Their ability to sensitively and specifically localize various tumor types could significantly improve patient outcome. Although further testing will be needed for regulatory approval, preliminary toxicity studies have indicated that these gold/silica-based NPs are chemically inert and show no significant toxicity in cell culture or in murine models after intravenous administration. , We wanted to be able to detect and deconvolve all 26 SERS NPs in the presence of the native tissue background in a living subject.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This NIR-II SERS probe could also delineate the tumor margin directly in a living mouse model following the intravenous administration. The non-invasive SERS imaging capability of our NIR-II SERS probes in living animals opens up an opportunity to intraoperative guidance of complete tumor resection and longitudinal monitoring of cancer therapeutic response 6 8 , 53 . We find that the tumor accumulation of NIR-II SERS probes declines over prolonging time following intravenous administration, so that longitudinal SERS imaging should be performed prior to metabolic elimination of NIR-II SERS probes from the tumors.…”
Section: Resultsmentioning
confidence: 99%